Anti-Inflammatory Effects of Aster incisus through the Inhibition of NF-κB, MAPK, and Akt Pathways in LPS-Stimulated RAW 264.7 Macrophages - Ngabire, Daniel; Seong, Yeong-Ae; Patil, Maheshkumar Prakash; Niyonizigiye, Irvine; Seo, Yong Bae; Kim, Gun-Do (Mediators of Inflammation, 2018)
Aster incisus is a common flower found in almost all regions of South Korea. In the current study, we investigated the potential antioxidant and anti-inflammatory properties of the Aster incisus methanol extract in LPS-stimulated RAW 264.7 cells. We analyzed the phytochemicals contained in the extract by GC-MS. GC-MS results showed that the Aster incisus extract contains 9 known compounds. Later on, DPPH assay, WST-1 assay, nitric oxide (NO) assay, Western blot, and RT-PCR were conducted to investigate the anti-inflammatory effects of the extract. Our WST-1 assay results revealed that Aster incisus did not affect the viability of all tested cell lines up to a concentration of 200 μg/ml; therefore, lower concentrations (50 μg/ml and 150 μg/ml) were used for further assays. Aster incisus scavenged DPPH and inhibited the production of NO. Aster incisus also reduced significantly the production of inflammation-related enzymes (iNOS, Cox-2) and cytokines (TNFα, IL-1β, and IL-6) and the gene expression of the proinflammatory cytokines. Additionally, further Western blot results indicated that Aster incisus inhibited the expression of p-PI3K, p-IκBα, p-p65 NF-κB, p-ERK1/2, p-SAPK/JNK, and p-Akt. Our results demonstrated that Aster incisus suppressed the expression of the inflammation mediators through the regulation of NF-κB, MAPK, and Akt pathways.